Understanding differentiated learning for primary education students as prospective teachers - Abdullah, Suhardi; Nurharyanto, Dwi Widyastuti; Hasanuddin , M. Irfan; Agustina, Eka; Nursyabani, Kyla Putri (Jurnal Prima Edukasia, 2026)
This study aims to measure the understanding of differentiated learning (DL) among primary education students as primary school teachers. Most research focuses on its implementation in schools, but rarely examines the extent to which prospective teachers are prepared to implement the curriculum. DL implementation in elementary and secondary education units is a particular concern for prospective teacher students. Curriculum changes also impact learning outcomes at the university level. Universities strive to produce outcomes that align with the needs of their respective fields. Teaching materials at universities need to adapt to DL as well. Students also need to become accustomed to new learning outcomes, namely being able to master, design, and practice all learning tools related to DL. The research method employed was a qualitative description, utilizing 107 multiple-choice questions. A total of 30 students became the subjects of this study. The questions given to students were adapted from the DL implementation book, which has six chapters. The score given was 1 for correct answers and 0 for incorrect ones. Therefore, each question received a score of 30 if it could be answered correctly by all students. The study’s results indicate that students’ understanding of DL remains low. The understanding of prospective teacher students in the PGSD study program, particularly at Khairun University, needs to be improved. Starting from the DL background, theoretical and empirical studies, and DL implementation, consisting of various types of grouping. For the scores obtained by students, 13 students achieved a correct score of 50% or above. If calculated overall, the classical achievement percentage was 43.33%.